Assessment Severity of Community Acquired Pneumonia By Curb-65 - Al.Obaidy, Muhammed W.; Abdulla, Ahmad T.; Sultan, Kassim M. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Community acquired pneumonia is the most frequent infection-related cause of death. Illness severity might usefully guide a number of management decisions and predict mortality. Confusion, blood urea ,respiratory rate ,blood pressure and age 65 years or older (CURB-65) based largely on clinical assessment. Objective: To evaluate the efficacy of CURB-65 score in assessment severity of community-acquired pneumonia and to predict mortality. Patients and Methods: Fifty patients were enrolled in this prospective study between 1st. of March 2007 and 31st. of January 2008, recruited at Baghdad Teaching Hospital diagnosed as community acquired pneumonia depending on having lower respiratory tract infection symptoms , signs and new infiltrate on the chest radiograph.CURB-65 scoring system was applied and the patients were divided into three groups low risk[CURB-65= (0-1)], intermediate risk [CURB-65= (2)], and high risk [CURB-65= (3-5)] groups . The low risk group was managed at home with oral antibiotics, the intermediate and high risk groups were managed at hospital with intravenous antibiotics. The 30-day mortalities were established. Results: There were 27(54%) females and 23 (46%) males at a median age of 68 year range from(15-90) year Thirty three patients (66%) had their age 65or older, 26 patients (52%) had B.U>7mmol/l, 11patients (22%) had R.R> 30/minute, 3 patients (6%) had systolic B.P<90 mm Hg, 11patients(22%) had diastolic B.P<60 mm Hg and 14 patients (28%) had confusion. Twenty patients (40%) were in the low risk group (CURB-65=0-1), 12 patients (24%) were in the intermediate risk group (CURB-65=2) and 18 patients (36%) were in the high risk group (CURB-65=3-5). The 30 day mortalities were (0%) in the low risk group, (16.5%) in the intermediate risk group and (30%) in the high risk. The overall mortality was 8 (16%) patients. Conclusion: CURB-65 effectively stratified patients regarding the site of medical care, type . route of administration of treatment and predicted mortality.